Cotton-Textile-Apparel sectors of Pakistan: Situations and challenges faced - Cororaton, Caesar B.; Salam, Abdul; Altaf, Zafar; Orden, David; Dewina, Reno; Minot, Nicholas; Nazli, Hina (International Food Policy Research Institute, 2008)
Cotton, textiles, and apparel are critical agricultural and industrial sectors in Pakistan. This study provides descriptions of these sectors and examines the key developments emerging domestically and internationally that affect the challenges and opportunities they face. One-quarter of Pakistani farmers, of whom about 40 percent have household incomes below the poverty line, grow cotton. Export controls and taxes kept cotton prices below international levels until the mid-1990s but have subsequently tracked export parity international levels following reforms to trade and pricing policies and a greater role for the private sector. Pakistani farmers have not formally adopted genetically modified Bt cotton but there is some field evidence of its unregulated use. Despite constraints in its production, storage, and ginning sectors, the production of cotton yarn increased at an annual rate of 4.7 percent during 1990-2005 and Pakistan's share of world output increased to nearly 10 percent. Cotton-related products account for nearly 60 percent of Pakistan's export earnings. The textile industry still produces mostly fabrics of relatively low count (low quality) although it has been successful in expanding its exports of some higher-value products. The industry will need further entrepreneurial initiatives to remain competitive in international markets. Among the farm households that produce cotton, about 40 percent of total income comes from its production. The decline in world prices that occurred in the late 1990s adversely affected these households. Household-level simulations suggest that a counterfactual 20 percent increase of cotton prices, which reflects the extent to which real cotton prices declined in Pakistan during this period, would have reduced the percentage of cotton-producing households below the poverty line in 2001 from 40 percent to 28 percent. The estimated effect from declining cotton prices explains about one-sixth of the overall observed increase of rural poverty in the period.